2008
DOI: 10.1016/j.neuint.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 and TNFα potentiate nitric oxide production in astrocyte cultures by recruiting distinct subpopulations of cells to express NOS-2

Abstract: Nitric oxide (NO) synthase-2 (NOS-2), a key source of NO at sites of neuroinflammation, is induced in astrocyte cultures treated with lipopolysaccharide (LPS) plus interferon-γ (IFNγ). A recent study examining the regulation of astrocytic NOS-2 expression demonstrated that transforming growth factor-β1 (TGFβ1) potentiated LPS plus IFNγ-induced NOS-2 expression via expansion of the pool of astrocytes that express NOS-2. Results in the current report indicate that this population-based mechanism of increasing NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 104 publications
3
17
0
Order By: Relevance
“…To the best of our knowledge, this is the first report demonstrating TGF-β1 elevation in ICV-OKA rats. TGF β1 and TNFalpha are also known to potentiate nitric oxide production in astrocyte cultures by recruiting distinct sub populations of cells to express nitric oxide synthase-2 (Hamby, Gragnolati, Hewett, & Hewett, 2008). Our findings are further supported by results from Kim, Kwak, Wang, and Choi (2008), who demonstrated that PP2A is a negative regulator of TGF-β1 and activation of TGF-β1-linked apoptotic signalling by TAK1 activation.…”
Section: Discussionsupporting
confidence: 85%
“…To the best of our knowledge, this is the first report demonstrating TGF-β1 elevation in ICV-OKA rats. TGF β1 and TNFalpha are also known to potentiate nitric oxide production in astrocyte cultures by recruiting distinct sub populations of cells to express nitric oxide synthase-2 (Hamby, Gragnolati, Hewett, & Hewett, 2008). Our findings are further supported by results from Kim, Kwak, Wang, and Choi (2008), who demonstrated that PP2A is a negative regulator of TGF-β1 and activation of TGF-β1-linked apoptotic signalling by TAK1 activation.…”
Section: Discussionsupporting
confidence: 85%
“…There is not a consensus whether inflammation induces oxidative stress or vice versa, since TLR4 cascade is involved in both events [63]. In this sense, ROS overproduction is able to increase TNF-a levels [64,65]. Our results show that resveratrol prevented the LPS-induced GSH content decrease through HO-1.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, we found significant elevation in TGF-β1 levels rat brain administered ICV Aβ 1-42 which was significantly attenuated on treatment with lycopene. TGF β 1 and TNF-α are also known to potentiate NO production in astrocyte cultures by recruiting distinct subpopulations of cells to express NO synthase-2 [73].…”
Section: Discussionmentioning
confidence: 99%